2009
DOI: 10.1111/j.1099-0860.2008.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Child Marriage or Forced Marriage? South Asian Communities in North East England

Abstract: This article addresses the links between child marriage and forced marriage in the UK, drawing from a research study on South Asian communities in North East England. It looks at definitional issues through an analysis of UK and South Asian policies. It also analyses how these concepts are understood by service providers, survivors of child marriage and young people from South Asian communities. Finally, concepts such as gender, age, familial and community control reflected in normative marriage practices are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 6 publications
2
51
1
2
Order By: Relevance
“…It has also been suggested that forced marriage is a product of immigration rather than a 'tradition' exported from the country of origin (Phillips and Dustin, 2004: 543). There is also literature addressing how forced marriage is against the tenets of different religions including Islam (Caroll, 1998) and a misinterpretation of culture (Gangoli et al, 2006). By looking across a range of communities involving different minority ethnic groups and different religions, the current study was able to examine some of these issues, as discussed below.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…It has also been suggested that forced marriage is a product of immigration rather than a 'tradition' exported from the country of origin (Phillips and Dustin, 2004: 543). There is also literature addressing how forced marriage is against the tenets of different religions including Islam (Caroll, 1998) and a misinterpretation of culture (Gangoli et al, 2006). By looking across a range of communities involving different minority ethnic groups and different religions, the current study was able to examine some of these issues, as discussed below.…”
Section: Discussionmentioning
confidence: 96%
“…The availability of certain support and services may be crucial to decreasing the risk of forced marriages taking place (Gangoli et al, 2006). Individuals may thus experience greater risks if they are unable to access appropriate services.…”
Section: Risk Factors Associated With Access To Servicesmentioning
confidence: 99%
See 3 more Smart Citations